High-durability non-woven fabric grinding pad and preparation method thereof
By using coatings of non-woven substrates and nano-silicon dioxide, such as nylon fiber and polyester fiber, the problem of non-woven abrasive pad coating is solved, and higher durability and more uniform abrasive effect are achieved.
Patent Information
- Application Number
- CN202510262943.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-22
AI Technical Summary
The adhesion between the coating of the existing non-woven abrasive pad and the substrate is insufficient, resulting in the coating being easily peeled off and affecting the service life of the abrasive pad.
A non-woven fabric is made of nylon fiber and polyester fiber, and nano-silica, modified glass fiber, water-based polyurethane resin, modified gypsum powder and aluminum powder are added to the coating to enhance the adhesion and overall performance between the coating and the substrate.
Improves the durability and tear resistance of the abrasive pad, extends service life, and improves uniformity and consistency of the abrasive effect.
Smart Images

Figure BDA0005300386320000091 
Figure BDA0005300386320000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polishing pads, and in particular to a highly durable non-woven polishing pad and a preparation method thereof. Background Art
[0002] Abrasive pads are tools used for grinding and polishing. They are widely used in many industrial fields such as optics, electronics, semiconductors, ceramics, etc. Abrasive pads can be divided into many types, such as polyurethane polishing pads, diamond polishing pads, non-woven polishing pads, damping cloth polishing pads, and honeycomb polishing pads.
[0003] Among them, the non-woven polishing pad is made of non-woven fabric material, has good flexibility and adaptability, and is suitable for grinding and polishing of various materials. Non-woven fabric is selected as the substrate, and abrasive particles (such as silicon carbide, aluminum oxide, etc.) and adhesives (such as polyurethane resin, etc.) are selected and mixed evenly, and then coated on the non-woven fabric substrate to obtain a polishing pad. The porous structure of the non-woven fabric makes it have good air permeability, which is conducive to the penetration and discharge of the polishing liquid and improves the polishing effect.
[0004] However, in the prior art, if the material selected for the non-woven fabric is not good enough, the adhesion between the coating and the non-woven fabric is insufficient, and the coating on the surface thereof is easy to fall off, thereby affecting the service life of the polishing pad. Summary of the invention
[0005] In order to improve the problem of insufficient adhesion between the coating and the non-woven fabric due to the poor material selection of the non-woven fabric, the present application provides a highly durable non-woven fabric polishing pad and a preparation method thereof.
[0006] The present application provides a highly durable non-woven abrasive pad, which adopts the following technical solution: A highly durable non-woven polishing pad comprises a substrate and a coating, wherein the substrate is woven from nylon fibers and polyester fibers, and the coating comprises the following raw materials, measured in parts by weight: 15-20 parts of nano silicon dioxide, 8-12 parts of modified glass fibers, 10-15 parts of waterborne polyurethane resin, 6-10 parts of modified gypsum powder, and 3-5 parts of aluminum powder.
[0007] By adopting the above technical solution, the substrate is a non-woven fabric woven from nylon fibers and polyester fibers, forming a non-woven fabric substrate with multiple properties such as softness, breathability, wear resistance, and tensile strength. Both nylon fibers and polyester fibers have high strength and wear resistance. The interweaving of these two fibers makes the grinding pad have excellent durability and tear resistance, and can withstand high loads and friction during the grinding process. The interwoven fiber structure helps the grinding pad maintain a stable shape during use and is not easily deformed or damaged, thereby ensuring the uniformity and consistency of the grinding effect.
[0008] The coating is a layer of material applied to the non-woven fabric substrate to enhance the overall effect of the grinding pad. Among the raw materials of the coating, nano-silicon dioxide increases the hardness and wear resistance of the coating. Its tiny particle size and high specific surface area provide a uniform grinding effect during the grinding process. It can also fill the micropores on the surface of the coating to form a dense coating structure, reduce scratches and damage during the grinding process, and improve the grinding quality. In addition, nano-silicon dioxide can physically and chemically interact with the surface of the non-woven fabric substrate during the coating formation process, thereby enhancing the adhesion between the coating and the substrate, helping to reduce the possibility of coating peeling and falling off, and improving the overall performance of the grinding pad. Nano-silicon dioxide reduces wear by rolling and filling particles during friction and wear, and has certain self-healing properties.
[0009] The modified glass fiber has high strength and hardness, which can better withstand the wear and friction during the grinding process, and is not easy to shift or slide due to friction, thereby improving the stability of the grinding process and increasing the roughness of the coating surface, thereby improving the anti-slip property, and then increasing the hardness and durability of the non-woven grinding pad. In addition, the modified glass fiber has excellent wear resistance and heat resistance, which improves the strength and toughness of the grinding pad coating, making it more able to withstand various mechanical stresses during the grinding process. The water-based polyurethane resin has good bonding properties, wear resistance and hardness, and can be firmly attached to the non-woven fabric substrate, increasing the close bonding between the coating and the substrate, and improving the overall strength and durability of the grinding pad. The modified gypsum powder can fill the tiny gaps in the coating, making the coating surface smoother, while increasing the hardness and roughness of the coating. The modified gypsum powder also has strong water absorption, absorbing moisture in the coating and moisture in the air, and keeping the surface of the grinding pad dry.
[0010] In addition, after the modified gypsum powder is mixed with the water-based polyurethane resin raw material, a tighter coating structure can be formed, which enhances the adhesion between the coating and the non-woven fabric substrate, helps the coating to adhere more firmly to the surface of the polishing pad during use, and reduces the possibility of falling off and wear. Aluminum powder can form a continuous metal film in the coating, which helps to improve the heat resistance of the coating. The coating obtained by combining various raw materials in this application has excellent wear resistance, heat resistance, and self-healing properties, which extends the durability of the polishing pad.
[0011] Preferably, the method for preparing the modified glass fiber comprises the following steps: (1) dispersing glass fibers in a sodium hydroxide solution, stirring at a temperature of 65-70° C. for 1-2 hours, washing with water, and drying to obtain pretreated glass fibers; (2) immersing the carbon fiber in aqua regia, stirring at 70-75° C., reflux reaction for 8-10 min, cooling, washing, filtering, and drying to obtain pretreated carbon fiber; (3) Dispersing the pretreated glass fiber of step (1) in deionized water, adding the pretreated carbon fiber of step (2), ultrasonicating for 1-2 hours, adding modified polyethylene glycol, stirring at a temperature of 60-65° C. for 30-35 minutes, drying and grinding to obtain modified glass fiber.
[0012] By adopting the above technical solution, the sodium hydroxide solution erodes the surface of the glass fiber, increases the surface roughness of the glass fiber, increases the number of active groups on the surface of the glass fiber, and helps to improve the interface compatibility and bonding strength between the glass fiber and other materials. Aqua regia removes metal impurities or metal oxides on the surface of the carbon fiber, produces a certain etching effect on the surface of the carbon fiber, increases the roughness of the carbon fiber surface, and improves the bonding strength between the carbon fiber and the matrix material.
[0013] Pretreated glass fiber is dispersed in deionized water, and pretreated carbon fiber is added. The pretreated carbon fiber can be loaded on the surface and pores of the pretreated glass fiber. The carbon fiber has high strength and high rigidity, and the glass fiber has good toughness. The carbon fiber and the glass fiber are composited to enhance the toughness and strength of the glass fiber. The modified polyethylene glycol has certain adhesion and can form a thin adhesion layer between the glass fiber and the carbon fiber, which helps to improve the interface bonding between the fibers, so that the carbon fiber and the glass fiber are tightly bonded, and the strength and stability of the overall material are improved. It is subsequently applied to the polishing pad coating to improve the hardness, wear resistance and strength of the coating, making the polishing pad more durable.
[0014] Preferably, the mass ratio of the glass fiber, the carbon fiber and the modified polyethylene glycol is 1:0.4-0.6:0.1-0.2.
[0015] By adopting the above technical scheme, the mass ratio of glass fiber, carbon fiber and modified polyethylene glycol is further limited within a certain range, so as to improve the strength and wear resistance of glass fiber. Glass fiber has high strength and high toughness, carbon fiber has high strength and high stiffness, carbon fiber can be loaded on the surface of glass fiber, so as to improve the strength and wear resistance of glass fiber. Modified polyethylene glycol has certain adhesion, so that carbon fiber and glass fiber are closely bonded, so as to improve the strength and stability of the whole system. It can be subsequently applied to the polishing pad coating, so as to effectively improve the hardness and wear resistance of the polishing pad coating, extend the service life of the polishing pad, improve the uniformity of the polishing pad coating, make it more flat and smooth, thereby improving the polishing quality.
[0016] Preferably, the method for preparing the modified polyethylene glycol comprises the following steps: dispersing polyethylene glycol in lactic acid, stirring at 80-85° C. for 1-2 hours, adding silicon carbide and polyvinyl pyrrolidone, stirring for 3-4 hours, and obtaining the modified polyethylene glycol.
[0017] By adopting the above technical scheme, polyethylene glycol is dispersed in lactic acid. Lactic acid has good solubility and biocompatibility, can dissolve polyethylene glycol, and helps to evenly disperse polyethylene glycol. Silicon carbide has excellent hardness and wear resistance, is dispersed in the system, and improves the strength and wear resistance of the system. Polyvinyl pyrrolidone has good film-forming property, dispersibility, hydrophilicity and biocompatibility, can promote the uniform dispersion of silicon carbide in polyethylene glycol, and also helps to form a more stable and uniform dispersion system; in addition, polyvinyl pyrrolidone can also improve the film-forming property and lubricity of modified polyethylene glycol, which is helpful for the subsequent application of modified polyethylene glycol in modified glass fiber, helps to improve the dispersibility of the system, and improves the strength and wear resistance of the system.
[0018] Preferably, the method for preparing the modified gypsum powder comprises the following steps: (1) calcining the desulfurized gypsum at 300-320° C. for 1-2 h, ball milling, and sieving to obtain pretreated gypsum powder; (2) dispersing the graphene in a sulfuric acid solution, stirring for 2-3 hours, washing with water, and then dispersing the graphene in an ammonia solution, stirring for 1-2 hours, and washing with water to obtain pretreated graphene; (3) dispersing the pretreated gypsum powder of step (1) in deionized water, adding the pretreated graphene of step (2), stirring at a temperature of 65-70° C. for 1-2 h, adding modified starch, stirring for 2-3 h, drying, and grinding to obtain modified gypsum powder.
[0019] By adopting the above technical solution, the desulfurized gypsum is calcined at 300-320°C, and the crystal water in the desulfurized gypsum will be gradually removed. The dehydrated gypsum powder has better physical and chemical properties, and the particles are more evenly dispersed. Ball milling further refines the particles and increases their specific surface area, thereby improving their reaction activity.
[0020] The graphene is first treated with a sulfuric acid solution to remove some impurities on the graphene surface and promote the dispersion of the graphene through its strong oxidizing property. It is then treated with an ammonia solution to neutralize the acidic substances that may remain in the previous sulfuric acid treatment process and help to further clean the graphene surface. The obtained pretreated graphene has good dispersibility and stability.
[0021] Pretreated gypsum powder is dispersed in deionized water, pretreated graphene is added, gypsum powder particles are uniformly dispersed in deionized water to form a stable suspension, graphene is uniformly dispersed in the gypsum powder suspension, heating and stirring promote the interaction between graphene and gypsum powder particles, graphene increases the strength and toughness of gypsum powder, and modified starch increases the viscosity of the gypsum system, ensuring that starch is uniformly dispersed in the mixture and fully in contact with graphene and gypsum powder particles. The obtained modified gypsum powder has good strength and toughness, and is subsequently applied to the coating of the grinding pad to increase the strength and wear resistance of the coating, so that the grinding pad can maintain a longer service life during use; moreover, the components in the modified gypsum powder can form good chemical bonding and physical adsorption with the grinding pad substrate, enhance the adhesion of the coating to the substrate, help avoid the coating from falling off or peeling off during use, and improve the overall performance of the grinding pad.
[0022] Preferably, the mass ratio of the desulfurized gypsum, graphene and modified starch is 1g:15-20mg:0.2-0.4g.
[0023] By adopting the above technical scheme, the mass ratio of desulfurized gypsum, graphene and modified starch is further limited within a certain range, and the obtained modified gypsum powder has good strength and wear resistance. Graphene is dispersed in the gypsum system to improve the strength and wear resistance of the system. The modified starch is in full contact with the graphene and gypsum powder particles to increase the viscosity of the gypsum system. The modified gypsum powder obtained by drying and grinding has good strength and toughness and is subsequently applied to the grinding pad coating to increase the strength and wear resistance of the coating.
[0024] Preferably, the preparation method of the modified starch comprises the following steps: dispersing starch in deionized water, adding microcrystalline corundum and gelatin, stirring at a temperature of 70-75° C. for 1-2 hours, drying, and grinding to obtain the modified starch.
[0025] By adopting the above technical scheme, starch is dispersed in deionized water so that starch particles can be evenly dispersed in the water, and microcrystalline corundum and gelatin are added. The microcrystalline corundum has good hardness and wear resistance and can be dispersed in the starch structure to improve the strength and toughness of the starch system. The gelatin has good film-forming and adhesive properties and helps to interact with starch particles and increase the viscosity of the starch system. After drying and grinding, the modified starch has good strength and wear resistance.
[0026] Preferably, the step of weaving the nylon fiber and the polyester fiber is: 6-10 nylon fibers are twisted into yarns for use as warp yarns, and 8-12 polyester fibers are twisted into yarns for use as weft yarns; The warp yarns and the weft yarns are woven together, with the warp yarn density being 350-370 yarns / 10 cm and the weft yarn density being 230-250 yarns / 10 cm, to obtain a substrate.
[0027] By adopting the above technical solution, nylon fiber has high strength and wear resistance, and the warp yarn made can withstand large tensile force and friction and is not easy to break. Polyester fiber has good wear resistance and strength. As weft yarn, it can be interwoven with nylon warp yarn to further enhance the overall strength and wear resistance of the substrate. The obtained substrate has good strength, wear resistance, elasticity and recovery.
[0028] Preferably, the thickness of the substrate is 0.3-0.5 mm, and the thickness of the coating is 1-1.5 mm.
[0029] By adopting the above technical solution and limiting the thickness of the substrate and the coating, the obtained non-woven fabric grinding pad has good support, moderate flexibility, and excellent wear resistance, thereby enhancing the durability and service life of the grinding pad.
[0030] In a second aspect, the present application also provides a method for preparing a highly durable non-woven abrasive pad, comprising the following steps: uniformly stirring nano-silicon dioxide, modified glass fiber, waterborne polyurethane resin, modified gypsum powder, aluminum powder and deionized water to obtain a coating mixture; The coating mixture is evenly coated on the substrate and dried at a temperature of 75-80° C. for 2-3 hours to obtain a non-woven polishing pad.
[0031] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing highly durable non-woven grinding pads. The obtained highly durable non-woven grinding pads have good mechanical properties, wear resistance and durability.
[0032] In summary, this application has the following beneficial effects: 1. The substrate in the present application is a non-woven fabric woven from nylon fibers and polyester fibers, forming a non-woven fabric substrate with multiple properties such as softness, breathability, wear resistance, and tensile strength. Both nylon fibers and polyester fibers have high strength and wear resistance. The interweaving of these two fibers makes the polishing pad have excellent durability and tear resistance, and can withstand high loads and friction during the grinding process.
[0033] 2. The nano-silica in this application can physically and chemically interact with the surface of the non-woven fabric substrate during the coating formation process, thereby enhancing the adhesion between the coating and the substrate, helping to reduce the possibility of coating peeling and shedding, and improving the overall performance of the polishing pad.
[0034] 3. The modified glass fiber in this application has high strength and hardness, can better withstand the wear and friction during the grinding process, is not easily displaced or slipped due to friction, improves the stability of the grinding process, increases the roughness of the coating surface, thereby improving the anti-slip properties, and further increases the hardness and durability of the non-woven grinding pad. DETAILED DESCRIPTION
[0035] The present application is further described in detail below with reference to the embodiments.
[0036] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0037] Preparation example of modified glass fiber Preparation Example 1-1 The preparation method of modified glass fiber comprises the following steps: (1) dispersing 1.5 kg of glass fiber in 2 L of 10% by mass sodium hydroxide solution, stirring at 70° C. for 1.5 h, washing with water, and drying to obtain pretreated glass fiber; (2) Immersing the carbon fiber in 3.5 L of aqua regia, stirring at 70° C. for 20 min, reflux reaction for 10 min, cooling, washing, filtering, and drying to obtain pretreated carbon fiber; wherein the aqua regia is a volume ratio of concentrated hydrochloric acid to concentrated nitric acid of 3:1, the mass fraction of concentrated hydrochloric acid is 38%, and the mass fraction of concentrated nitric acid is 68%.
[0038] (3) Disperse the pretreated glass fiber of step (1) in 5 L of deionized water, add the pretreated carbon fiber of step (2), ultrasonicate for 2 h, add modified polyethylene glycol, stir for 35 min at 65 ° C, dry and grind to obtain modified glass fiber.
[0039] The mass ratio of glass fiber, carbon fiber and modified polyethylene glycol is 1:0.4:0.1.
[0040] The preparation method of modified polyethylene glycol comprises the following steps: dispersing 1 kg of polyethylene glycol in 2 L of lactic acid, stirring at 85° C. for 1.5 h, adding 0.4 kg of silicon carbide and 0.2 kg of polyvinyl pyrrolidone, stirring for 4 h, and obtaining modified polyethylene glycol; wherein the particle size range of silicon carbide is 0.2-0.5 μm, and lactic acid is purchased from Shandong Yijia Chemical Co., Ltd.
[0041] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no carbon fiber is added.
[0042] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no modified polyethylene glycol is added.
[0043] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of glass fiber, carbon fiber and modified polyethylene glycol is 1:0.6:0.2.
[0044] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of glass fiber, carbon fiber and modified polyethylene glycol is 1:0.1:0.5.
[0045] Preparation Example 1-6 The difference from Preparation Example 1-1 is that silicon carbide is not added in the preparation method of modified polyethylene glycol.
[0046] Preparation Example 1-7 The difference from Preparation Example 1-1 is that in the preparation method of modified polyethylene glycol, polyvinyl pyrrolidone is not added.
[0047] Preparation example of modified gypsum powder Preparation Example 2-1 The preparation method of modified gypsum powder comprises the following steps: (1) 1.8 kg of desulfurized gypsum was calcined at 310° C. for 1.5 h, ball-milled, and passed through a 250-mesh sieve to obtain pretreated gypsum powder; the desulfurized gypsum was purchased from Kunjian Mineral Products Processing Plant in Lingshou County; (2) dispersing the graphene in 1L of 80% sulfuric acid solution, stirring for 2.5h, washing with water, and then dispersing 1.1L of 25% ammonia solution, stirring for 1.5h, and washing with water to obtain pretreated graphene; (3) Dispersing the pretreated gypsum powder of step (1) in 5 L of deionized water, adding the pretreated graphene of step (2), stirring at a temperature of 70° C. for 1.5 h, adding modified starch, stirring for 2.5 h, drying, and grinding to obtain modified gypsum powder.
[0048] The mass ratio of desulfurized gypsum, graphene and modified starch is 1g:15mg:0.4g.
[0049] The preparation method of modified starch comprises the following steps: dispersing 1.2 kg of starch in 2.5 L of deionized water, adding 0.5 kg of microcrystalline corundum and 0.3 kg of gelatin, stirring at a temperature of 75° C. for 1.5 hours, drying, and grinding to obtain modified starch.
[0050] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no graphene is added.
[0051] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (3), no modified starch is added.
[0052] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of desulfurized gypsum, graphene and modified starch is 1g:20mg:0.2g.
[0053] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of desulfurized gypsum, graphene and modified starch is 1g:10mg:0.6g.
[0054] Preparation Example 2-6 The difference from Preparation Example 2-1 is that in the preparation method of the modified starch, no microcrystalline corundum is added.
[0055] Preparation Example 2-7 The difference from Preparation Example 2-1 is that gelatin is not added in the preparation method of the modified starch. Example
[0056] Example 1 A highly durable non-woven polishing pad comprises a substrate and a coating, wherein the substrate is woven from nylon fibers and polyester fibers, and the coating comprises the following raw materials by weight: 15 kg of nano silicon dioxide, 8 kg of modified glass fibers, 10 kg of waterborne polyurethane resin, 6 kg of modified gypsum powder, and 3 kg of aluminum powder, wherein the particle size of the silicon dioxide particles ranges from 10 to 20 nm, and the waterborne polyurethane resin is purchased from Guangdong Xidun New Material Technology Co., Ltd.
[0057] Steps for weaving nylon fiber and polyester fiber: Nine nylon fibers are twisted into yarns for use as warp yarns, and 11 polyester fibers are twisted into yarns for use as weft yarns; The warp yarns and the weft yarns were woven together, with the warp yarn density being 360 yarns / 10 cm and the weft yarn density being 240 yarns / 10 cm, to obtain a base material.
[0058] The preparation method of the above-mentioned highly durable non-woven polishing pad comprises the following steps: uniformly stirring nano-silicon dioxide, modified glass fiber, water-based polyurethane resin, modified gypsum powder, aluminum powder and 80 kg of deionized water to obtain a coating mixture; uniformly coating the coating mixture on a substrate, drying at a temperature of 80° C. for 3 hours to obtain a non-woven polishing pad, wherein the thickness of the substrate is 0.4 mm and the thickness of the coating is 1.2 mm.
[0059] The modified glass fiber was prepared by using Preparation Example 1-1; and the modified gypsum powder was prepared by using Preparation Example 2-1.
[0060] Example 2 A highly durable non-woven fabric polishing pad, which differs from Example 1 in that the coating, by weight, comprises the following raw materials: 20 kg of nano silicon dioxide, 12 kg of modified glass fiber, 15 kg of waterborne polyurethane resin, 10 kg of modified gypsum powder, and 5 kg of aluminum powder.
[0061] Example 3 A highly durable non-woven polishing pad, which is different from Example 1 in that the modified glass fiber is prepared using Preparation Example 1-2.
[0062] Example 4 A highly durable non-woven polishing pad is different from Example 1 in that the modified glass fiber is prepared using Preparation Examples 1-3.
[0063] Example 5 A highly durable non-woven fabric polishing pad is different from Example 1 in that the modified glass fiber is prepared using Preparation Examples 1-4.
[0064] Example 6 A highly durable non-woven fabric polishing pad is different from Example 1 in that the modified glass fiber is prepared using Preparation Examples 1-5.
[0065] Example 7 A highly durable non-woven polishing pad is different from Example 1 in that the modified glass fiber is prepared using Preparation Examples 1-6.
[0066] Example 8 A highly durable non-woven polishing pad is different from Example 1 in that the modified glass fiber is prepared using Preparation Examples 1-7.
[0067] Example 9 A highly durable non-woven fabric polishing pad, which is different from Example 1 in that the modified gypsum powder is prepared using Preparation Example 2-2.
[0068] Example 10 A highly durable non-woven fabric polishing pad, which is different from Example 1 in that the modified gypsum powder is prepared using Preparation Example 2-3.
[0069] Embodiment 11 A highly durable non-woven fabric polishing pad, which is different from Example 1 in that the modified gypsum powder is prepared using Preparation Examples 2-4.
[0070] Example 12 A highly durable non-woven fabric polishing pad, which is different from Example 1 in that the modified gypsum powder is prepared using Preparation Examples 2-5.
[0071] Example 13 A highly durable non-woven fabric polishing pad is different from Example 1 in that the modified gypsum powder is prepared using Preparation Examples 2-6.
[0072] Embodiment 14 A highly durable non-woven fabric polishing pad, which is different from Example 1 in that the modified gypsum powder is prepared using Preparation Examples 2-7.
[0073] Comparative Example Comparative Example 1 A highly durable nonwoven polishing pad, which differs from Example 1 in that no modified glass fiber is added.
[0074] Comparative Example 2 A highly durable nonwoven polishing pad, which differs from Example 1 in that the modified glass fiber is replaced by an equal amount of glass fiber.
[0075] Comparative Example 3 A highly durable non-woven fabric polishing pad, which differs from Example 1 in that no gypsum powder is added.
[0076] Comparative Example 4 A highly durable non-woven fabric polishing pad, which differs from Example 1 in that the modified gypsum powder is replaced by an equal amount of gypsum powder.
[0077] Performance testing The highly durable nonwoven polishing pads prepared in Examples 1-14 and Comparative Examples 1-4 were subjected to performance tests; The surface of the sample was dressed using a grinding wheel dresser under the conditions of forced drive speed of 110 rpm, platen speed of 60 rpm, dressing load of 7 pounds, water absorption of 200 mL / min, and dressing time of 30 min. The thickness was measured every 10 mm, for a total of 25 points. The difference (wear amount) in thickness from the undressed center was calculated at each measuring position, and the average value was obtained. Wear rate (μm / min) = average value of wear amount / (0.5×60).
[0078] Peel strength: The polishing pads (width 40 mm, length 40 mm) prepared in the examples and comparative examples were tested for peel strength (N / 25 mm) using a tensile tester (manufactured by Shimadzu Corporation) at a peel angle of 180° and a peel speed of 55 mm / min.
[0079] Peel strength retention rate = (peel strength value after grinding process / peel strength value before grinding process) × 100; the test results are shown in Table 1.
[0080] Table 1 Test data of embodiments and comparative examples As can be seen from Table 1, the polishing pads prepared in Examples 1-2 of the present application have good mechanical properties and wear resistance, wherein the wear rate of Example 1 is 2 μm / min, the polishing pad life is 3.3 h, the initial peel strength is 49.9 N / 25 mm, the peel strength after grinding is 48.9 N / 25 mm, and the retention rate is 98%. This indicates that the prepared highly durable non-woven polishing pad has good mechanical properties and mechanical strength, and the coating obtained by combining various raw materials in the present application has excellent wear resistance, heat resistance, and self-repairing properties, which prolongs the durability of the polishing pad.
[0081] In the preparation method of the modified glass fiber of Examples 3-4, carbon fiber and modified polyethylene glycol are not added respectively, and the mass ratio of glass fiber, carbon fiber and modified polyethylene glycol is changed in Examples 5-6. It can be seen from Table 1 that the test results of the wear rate, grinding pad life, initial peel strength, peel strength after grinding and retention rate of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the corresponding performance test of Example 6 is better than that of Examples 3-4, but worse than that of Examples 1 and 5, indicating that the carbon fiber can be loaded on the surface of the glass fiber to improve the strength and wear resistance of the glass fiber. The modified polyethylene glycol has certain adhesion, so that the carbon fiber and the glass fiber are closely bonded, and the strength and stability of the overall system are improved. It is subsequently applied to the grinding pad coating to improve the hardness and wear resistance of the grinding pad coating and extend the service life of the grinding pad.
[0082] In the preparation method of the modified polyethylene glycol of Examples 7-8, silicon carbide and polyvinyl pyrrolidone are not added respectively. As can be seen from Table 1, the test results of the wear rate, grinding pad life, initial peel strength, peel strength after grinding and retention rate are significantly worse than those of Examples 1-2, but better than those of Example 4, indicating that silicon carbide has excellent hardness and wear resistance, improves the strength and wear resistance of the system, and polyvinyl pyrrolidone improves the film-forming property and lubricity of the modified polyethylene glycol, helps to improve the dispersibility of the system, and improves the strength and wear resistance of the system.
[0083] In the preparation method of the modified gypsum powder of Examples 9-10, graphene and modified starch are not added respectively, and the mass ratio of desulfurized gypsum, graphene and modified starch is changed in Examples 11-12. It can be seen from Table 1 that the test results of the wear rate, grinding pad life, initial peel strength, peel strength after grinding and retention rate of Examples 9-10 are significantly worse than those of Examples 1-2 and Example 11, while the corresponding performance test of Example 12 is better than that of Examples 9-10, but worse than that of Examples 1 and 11, indicating that graphene is dispersed in the gypsum system, improving the strength and wear resistance of the system, and the modified starch is in full contact with the graphene and gypsum powder particles to increase the viscosity of the gypsum system. The modified gypsum powder has good strength and toughness, and is subsequently applied to the grinding pad coating to increase the strength and wear resistance of the coating.
[0084] In the preparation methods of the modified starches of Examples 13-14, microcrystalline corundum and gelatin are not added respectively. As can be seen from Table 1, the test results of the wear rate, grinding pad life, initial peel strength, peel strength after grinding and retention rate are significantly worse than those of Examples 1-2, but better than those of Example 10, indicating that microcrystalline corundum has good hardness and wear resistance, improves the strength and toughness of the starch system, and gelatin has good film-forming and adhesive properties, which helps to interact with starch particles and increase the viscosity of the starch system, so that the modified starch has good strength and wear resistance.
[0085] In Comparative Example 1 and Comparative Example 3, no modified glass fiber and modified gypsum powder are added, respectively. As can be seen from Table 1, the test results of the wear rate, grinding pad life, initial peel strength, peel strength after grinding and retention rate of Comparative Example 1 and Comparative Example 3 are significantly worse than those of Examples 1-2, indicating that the modified glass fiber has excellent wear resistance and heat resistance, and improves the strength and toughness of the grinding pad coating; the modified gypsum powder enhances the adhesion between the coating and the non-woven fabric substrate, which helps the coating to adhere more firmly to the surface of the grinding pad during use, reducing the possibility of falling off and wear.
[0086] In Comparative Examples 2 and 4, the modified glass fiber is replaced by an equal amount of glass fiber, and the modified gypsum powder is replaced by an equal amount of gypsum powder. It can be seen from Table 1 that compared with Example 1, the test results of the wear rate, grinding pad life, initial peel strength, peel strength after grinding and retention rate of Comparative Examples 2 and 4 are significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the modified glass fiber and modified gypsum powder of the present application have good mechanical properties, thereby improving the overall strength, wear resistance and durability of the grinding pad.
[0087] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A highly durable nonwoven polishing pad, characterized in that: The invention comprises a substrate and a coating, wherein the substrate is woven from nylon fiber and polyester fiber, and the coating comprises the following raw materials by weight: 15-20 parts of nano silicon dioxide, 8-12 parts of modified glass fiber, 10-15 parts of waterborne polyurethane resin, 6-10 parts of modified gypsum powder and 3-5 parts of aluminum powder.
2. A highly durable nonwoven polishing pad according to claim 1, characterized in that: The method for preparing the modified glass fiber comprises the following steps: (1) dispersing the glass fiber in a sodium hydroxide solution, stirring at a temperature of 65-70°C for 1-2 hours, washing with water, and drying to obtain pretreated glass fiber; (2) immersing the carbon fiber in aqua regia, stirring at 70-75° C., reflux reaction for 8-10 min, cooling, washing, filtering, and drying to obtain pretreated carbon fiber; (3) Dispersing the pretreated glass fiber of step (1) in deionized water, adding the pretreated carbon fiber of step (2), ultrasonicating for 1-2 hours, adding modified polyethylene glycol, stirring at a temperature of 60-65° C. for 30-35 minutes, drying and grinding to obtain modified glass fiber.
3. A highly durable nonwoven polishing pad according to claim 2, characterized in that: The mass ratio of the glass fiber, the carbon fiber and the modified polyethylene glycol is 1:0.4-0.6:0.1-0.
2.
4. A highly durable nonwoven polishing pad according to claim 2, characterized in that: The preparation method of the modified polyethylene glycol comprises the following steps: dispersing polyethylene glycol in lactic acid, stirring at 80-85° C. for 1-2 hours, adding silicon carbide and polyvinyl pyrrolidone, stirring for 3-4 hours, and obtaining the modified polyethylene glycol.
5. A highly durable nonwoven polishing pad according to claim 1, characterized in that: The preparation method of the modified gypsum powder comprises the following steps: (1) calcining the desulfurized gypsum at 300-320°C for 1-2h, ball milling, and sieving to obtain pretreated gypsum powder; (2) dispersing the graphene in a sulfuric acid solution, stirring for 2-3 hours, washing with water, and then dispersing the graphene in an ammonia solution, stirring for 1-2 hours, and washing with water to obtain pretreated graphene; (3) Dispersing the pretreated gypsum powder of step (1) in deionized water, adding the pretreated graphene of step (2), stirring at a temperature of 65-70° C. for 1-2 h, adding modified starch, stirring for 2-3 h, drying, and grinding to obtain modified gypsum powder.
6. A highly durable nonwoven polishing pad according to claim 5, characterized in that: The mass ratio of the desulfurized gypsum, graphene and modified starch is 1g:15-20mg:0.2-0.4g.
7. A highly durable nonwoven polishing pad according to claim 5, characterized in that: The preparation method of the modified starch comprises the following steps: dispersing starch in deionized water, adding microcrystalline corundum and gelatin, stirring at a temperature of 70-75° C. for 1-2 hours, drying, and grinding to obtain the modified starch.
8. A highly durable nonwoven polishing pad according to claim 1, characterized in that: The steps of weaving the nylon fiber and the polyester fiber are as follows: 6-10 nylon fibers are twisted into yarns to be used as warp yarns, and 8-12 polyester fibers are twisted into yarns to be used as weft yarns; The warp yarns and the weft yarns are woven together, with the warp yarn density being 350-370 yarns / 10 cm and the weft yarn density being 230-250 yarns / 10 cm, to obtain a substrate.
9. A highly durable nonwoven polishing pad according to claim 1, characterized in that: The thickness of the substrate is 0.3-0.5 mm, and the thickness of the coating is 1-1.5 mm.
10. The method for preparing a highly durable nonwoven polishing pad according to claim 1, characterized in that: The method comprises the following steps: uniformly mixing nano silicon dioxide, modified glass fiber, waterborne polyurethane resin, modified gypsum powder, aluminum powder and 3 deionized water to obtain a coating mixture; The coating mixture is evenly coated on the substrate and dried at a temperature of 75-80° C. for 2-3 hours to obtain a non-woven polishing pad.
Citation Information
Cited By
Multifunctional VAE composite wear-resistant nursing pad and preparation method thereof
CN120392424A